The Effect of Breast-feeding in Contraception which is a Method of Natural Family Planning - N İnce; B Özyildirim; E Işik; F Bozcali (Tehran University of Medical Sciences, 2007)
Background: Bongaarts's model of Ci calculation was used to calculate the contribution of breast-feeding to family planning. Methods: This cross-sectional  study was conducted in the area of  İstanbul (TURKEY) Silivri Public Health Practice and Research Center between the dates of 20th May-1st October 2005. In this study  whole under 1 year old babies, composed the sample (n=1247). Bongaarts model can be summarized as Total Fertility Rate (TFR)= TF x Ci x CA x CC x Cm and takes its bases from TF ( total fertility). Ci is the Postparum infekunditi index.  Ci= 20"(18.5+i) is calculated by this formula. The first menstruation period, after pregnancy ends, was taken as the value 'i'. Results: The average age for the total 1247 mothers who contributed to this study was 26.7±5.2 (R: 16 - 50) yr. The women whose menstruation turned back (n=830), the average amenore period was found as 3.0±1.9 (1-12 months). Ci's average value was 0.94±0.07 (0,66-1.03) and a r= -0.08, P= 0.012 correlation was appointed between mother's age and Ci. 7.7% of participants (n: 96) used breast-feeding as a contraceptive method. These participants used breast-feeding as contraception for 16.9±14.5 wk. Conclusions: Breast-feeding is a reliable and a positive affecting   method of family planning for both improving the baby and mother's health. Furthermore   also by affecting TFR over Ci, it provides a positive contribution to society health.